Molecular and chemical characterization of a Sphagnum palustre clone: Key steps towards a standardized and sustainable moss bag technique. (December 2016) - Di Palma, A.; Crespo Pardo, D.; Spagnuolo, V.; Adamo, P.; Bargagli, R.; Cafasso, D.; Capozzi, F.; Aboal, J.R.; González, A.G.; Pokrovsky, O.; Beike, A.K.; Reski, R.; et al.
Graphical abstract: Highlights: A Sphagnum palustre clone is proposed as valid candidate for active biomonitoring. A chemical and molecular characterization of the clone was performed. Five anonymous sequences and their primers were obtained as new molecular markers. Element concentration was stable and lower in the clone than in native S. palustre . Elemental composition was not significantly affected by oven and EDTA treatments. Abstract: This work aimed to define the molecular and chemical signature of a S. palustre clone developed in the framework of the EU-FP7 Mossclone project to improve the standardization and reliability of the moss-bag technique. The molecular characterization was performed by a set of DNA molecular markers (RAPD, ISJ, PCR-RFLP, sequencing and microsatellites) to tag the clone produced within the project. Molecular characterization also provided new DNA markers that can be applied in systematic analyses of Sphagnum, and gave new insights to implement well established techniques. The elemental composition of the clone was measured by ICP-MS analysis of 54 major and trace elements, with and without commonly applied pre-exposure treatments (oven devitalization and EDTA washing). Concentrations of almost all analyzed elements were significantly lower (from 10 to 100 times) in the clone than in conspecific field moss, apart from some elements (K, Mo, P and Na) deriving from the culture medium or EDTA treatment. Oven devitalization and EDTA washing did not significantly affect the clone composition. A comparison between the elemental composition of the clone with that of naturally growing Sphagnum species proved the particularly low elemental content of the clone. Therefore, in view of a rigorously standardized moss-bag protocol for the monitoring of persistent atmospheric pollutants, the use of the S. palustre clone, a biomaterial with very low and constant element composition, and homogenous morphological characteristics is strongly recommended.